Penerapan Algoritma C4.5 pada Analisis Kerusakan Barang Jadi - Ivan Oktana; Seng Hansun (Ultima Computing : Jurnal Sistem Komputer, 2015)
A Data mining is the activity that includes the collection, the use of historical data to discover regularity, patterns and relationship in a large data set. The usefulness of data mining is to specify a pattern to be found in the data mining task. The presences of data mining is motivated by the problem of data explosion which had been experienced lately these day where many organization or company collect so many years of data (purchasing data, sales data, damage data item, transaction data, and so on). In this paper data mining methods been used to analyze the damage data of finished products, with the goal of producing a pattern of the damage product. Based on the pattern from product’s damage, can be see and the aspects that affect to the damaged product. The purpose of this study is to show information about the relationship of damage data of finished goods using C4.5 algorithms in PT. Kayu Lapis Asli Murni, and display results in the form of a decision tree mining. Index Terms—data mining, C4.5 algorithms, decision tree, damage data of finished products, PT. Kayu Lapis Asli Murni